Indonesian First Experiences in Delineating Extended Continental Shelf Submission to The UNCLOS - Sutisna, Sobar; Lokita, Sora (Indonesian Journal of International Law, 2021)
The international law, in particular the Law of the Sea Convention (hereinafter: LOSC), has provided a progresive development to Indonesia in the context its territory and jurisdiction. Indonesia as one of the parties of the United Convention on the Law of the Sea 1982 has the right to establish its maritime zones in accordance with the convention. One of those maritime zones is the continental shelf. The delineation of the outer limit of the continental shelf is referred to Article 76 of LOSC. With that regard, Indonesia has just recently completed a process of the first partial submission of its continental shelf beyond 200 nautical miles (ECS) at the United Nations-Commission on the Limits of the Continental Shelf (UN CLCS). The related ECS area for the first partial submission is located in northwest Sumatra Island. The completion of the first submission brought precious experiences for Indonesia, one of those is concerning the management of maritime boundary and territory. This paper discusses the Indonesian ECS and its submission process and all related matters. In addition, this paper hopefully useful for information sharing among stakeholder, and provide a brief summary for the history of the submission.